Worldwide Wound Healing - Innovation in Natural and Conventional Methods 2016
DOI: 10.5772/65652
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds for Wound Healing

Abstract: Many plants or plant-derived compounds with high levels of antioxidants and antiinflammatory, immunomodulatory, and antimicrobial properties could be of great benefit for wound healing. Several studies have documented the use of plant extracts for the development of bioactive wound dressings. The purpose of this chapter is to give an update about the vegetal and bee products, which can be used as bioactive substances in wound dressings or in other formulations for wound healing. The adverse effects of plant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 118 publications
0
12
0
1
Order By: Relevance
“…Previous reports showed that many wound healing herbs are rich in phenolic and flavonoid contents which play important roles in wound healing activity [ 4 , 25 , 36 ]. These compound effects on the wound healing process might be due to antioxidant, anti-inflammation, antimicrobial, angiogenesis, and cell proliferation stimulation activity [ 25 , 46 ]. In this study, our results showed that CCLE contains phenolic and flavonoid compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that many wound healing herbs are rich in phenolic and flavonoid contents which play important roles in wound healing activity [ 4 , 25 , 36 ]. These compound effects on the wound healing process might be due to antioxidant, anti-inflammation, antimicrobial, angiogenesis, and cell proliferation stimulation activity [ 25 , 46 ]. In this study, our results showed that CCLE contains phenolic and flavonoid compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants have been extensively used worldwide as traditional treatment for various diseases due to being a source of phytochemicals, which are nonnutritive substances present in plants enhancing tissue regeneration and acting as pro-angiogenic agents for wound healing. In addition, bioactive products extracted from plants arouse scientific and commercial interests for the development of new drugs [13]. On the other hand, plants are also source of many macromolecules such as carbohydrate and proteins extensively used as biomaterials for wound healing applications.…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…For R. nervosus leaves, a correlation was observed between the principal polyphenolic components (flavonols) of the extract and the antioxidant activity [244] (Table 2; Supplementary material, Table S1). The inhibitory effects of polyphenolic compounds against bacterial Alasbahi and Groot pathogens have been ascribed to their ability to attack several targets of pathogenic microorganisms such as the inhibition of nucleic acid synthesis, the perturbation of the cytoplasmatic membrane and thereby affecting the permeability and leading to intracellular constituent release and the inhibition of energetic metabolism and thus interfering with membrane functions such as electron transport, nutrient absorption, nucleic acid synthesis, and ATPase activity [277]. Although the precise mechanisms of the anti-inflammatory activity of phenolic compounds are not fully elucidated, it is has been hypothesized that phenolic compounds exert anti-inflammatory activity by inhibition the synthesis of pro-inflammatory mediators, modification of eicosanoid synthesis, inhibition of activated immune cells, or inhibition of nitric oxide synthase and COX-2 via the inhibitory effects on nuclear factor NF-κβ [278].…”
Section: •-mentioning
confidence: 99%